Sexual assault in the military a guide for victims and families - Lawhorne Scott, Cheryl 1968-; Philpott, Don 1946-; Scott, Jeff 1969- (Military life (Lanham, Md.), 2014)
Sexual assault and harassment in the military have been a critical subject for years. Many victims may be reluctant to press charges because of fear of retaliation, damage to their careers, and widespread uncertainty regarding the military justice system. However, when circumstances arise, there are resources available to assist victims and families in their efforts to report, seek help, and recover from the effects of sexual assault. Yet, finding those resources can be challenging, especially in a time of crisis. Sexual Assault in the Military serves as a reference guide for military members and their families about sexual assault and harassment. While more and more attention focuses on getting victims to report their abuse, accessing information can still be difficult for service members. Understanding that the military is making changes, and offering support is a necessary step towards how best to treat these cases and how to get help and justice. Cheryl Lawhorne-Scott and Don Philpott discuss the current state of affairs, the systems in place, and the supports available to victims and families. They provide documents that outline how reporting can and should take place, how cases should be handled through the military justice system, and how and where victims can access resources, including counseling.